Stretch Induces Invasive Phenotypes in Breast Cells Due to Activation of Aerobic‐Glycolysis‐Related Pathways. Issue 7 (7th May 2019) - Ansaryan, Saeid; Khayamian, Mohammad Ali; Saghafi, Mohammad; Shalileh, Shahriar; Nikshoar, Mohammad Saied; Abbasvandi, Fereshteh; Mahmoudi, Morteza; Bahrami, Farideh; Abdolahad, Mohammad
Abstract: It is increasingly being accepted that cells' physiological functions are substantially dependent on the mechanical characteristics of their surrounding tissue. This is mainly due to the key role of biomechanical forces on cells and their nucleus' shapes, which have the capacity to regulate chromatin conformation and thus gene regulations. Therefore, it is reasonable to postulate that altering the biomechanical properties of tissue may have the capacity to change cell functions. Here, the role of cell stretching (as a model of biomechanical variations) is probed in cell migration and invasion capacity using human normal and cancerous breast cells. By several analyses (i.e., scratch assay, invasion to endothelial barrier, real‐time RNA sequencing, confocal imaging, patch clamp, etc.), it is revealed that the cell‐stretching process could increase the migration and invasion capabilities of normal and cancerous cells, respectively. More specifically, it is found that poststretched breast cancer cells are found in low grades of invasion; they substantially upregulate the expression of manganese‐dependent superoxide dismutase (MnSOD) through activation of H‐Ras proteins, which subsequently induce aerobic glycolysis followed by an overproduction of matrix metalloproteinases (MMP)‐reinforced filopodias. Presence of such invadopodias facilitates targeting of the endothelial layer, and increased invasive behaviors in breast cells are observed. Abstract : Mechanical interactions between cells and their surrounding tissue play a pivotal role in cells' behavior. The effect of stretching stimuli, as a widespread but poorly understood mechanical stimulation, is investigated in healthy and canorous breast cells. It is revealed that such biomechanical variations can lead to an increase in migration and invasion capacity of normal and cancer cells, respectively.